(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
In this article, we will look at how you can choose a gift for a client that will not only please him, but also help draw his attention to your company. We will offer some key tips and ideas so that you can make the most of gifts as a marketing tool.